Food insecurity and the use of coping strategies on multimorbidity, anxiety and depression in South African adults: A nationally representative study - Olatundun Gafari; Ashleigh Craig; Khuthala Mabetha; Duncan Hornby; Craig Hutton; Mary Barker; Shane A. Norris (PLoS ONE, 2026)
Objective To assess the associations between food insecurity, coping strategies, socio-economic status and anxiety, depression and multimorbidity in South Africa. Methods Data from a nationally representative cross-sectional survey conducted in April 2024 (n = 3171; weighted to 20,955,234 adults aged > 18 years) were used. Food insecurity was measured using the Community Childhood Hunger Identification Project (CCHIP) tool, a validated household-level measure commonly used in South Africa. Coping strategy, anxiety and depression were measured using the coping strategies index, Generalised Anxiety Disorder–7 scale and Patient Health Questionnaire–9, respectively. Multimorbidity was self-reported as ≥2 of 14 known chronic conditions. Multivariable logistic regression was used to test associations, and a generalised structural equation model examined the roles of socio-economic status and coping strategies. Results Being from a food-insecure household more than doubled the odds of experiencing multimorbidity (OR=2.17, 95% CI 2.17, 2.19), depression (OR=2.96, 95% CI 2.95, 2.97) and anxiety (OR=2.82, 95% CI 2.81, 2.83). Food insecurity accounted for approximately 60% of the total association between socio-economic status and depression, and about 88% of the association between socio-economic status and multimorbidity. Conclusions Food insecurity is significantly associated with adverse physical and mental health outcomes. Interventions to improve food security, especially in low socio-economic populations, should be prioritised given their associations with multimorbidity, anxiety and depression. Potential intervention effects will require longitudinal or experimental evaluation.